Information technology as a support to the strategic management of information in small businesses (Journal of Information Systems and Technology Management, 2004)
The present article aims to discuss the contribution of information technology (IT) as a support to the strategic management of information in small businesses. This is a relevant subject to this sector, in which the information on the subjects is scarce and there is little knowledge of its relevance in the strategic process. Thus, most entrepreneurs do not visualize the information technology as a tool capable of aiding in the decision and strategic process, using it, many times, just in administrative and operational tasks. Another reason that contributes to a minor dissemination of the information technology in the small businesses segment is its lack of adaptation to the environment, where it is implemented without considering the principal management specificities of the small enterprises. The literature about the use of information technology in the strategic process of small organizations shows a series of obstacles to be overcome, such as: implementing financially accessible technologies, involving the entrepreneur in the implementation process and supplying adapted training to employees and entrepreneurs. Therefore, for small businesses it is relevant to develop researches that allow the adaptation of information technology to its needs to improve the strategic management.